Focal depth, magnitude, and frequency distribution of earthquakes along oceanic trenches (2013)
The occurrence of earthquakes in oceanic trenches can pose a tsunami threat to lives and properties in active seismic zones. Therefore, the knowledge of focal depth, magnitude, and time distribution of earthquakes along the trenches is needed to investigate the future occurrence of earthquakes in the zones. The oceanic trenches studied, were located from the seismicity map on: latitude +51˚ to +53˚ and longitude -160˚ to 176˚ (Aleutian Trench), latitude +40˚ to +53˚ and longitude +148˚ to +165˚ (Japan Trench), and latitude -75˚ to -64˚ and longitude –15˚ to +30˚ (Peru–Chile Trench). The following features of seismic events were considered: magnitude distribution, focal depth distribution, and time distribution of earthquake. The results obtained in each trench revealed that the earthquakes increased with time in all the regions. This implies that the lithospheric layer is becoming more unstable. Thus, tectonic stress accumulation is increasing with time. The rate of increase in earthquakes at the Peru–Chile Trench is higher than that of the Japan Trench and the Aleutian Trench. This implies that the convergence of lithospheric plates is higher in the Peru–Chile Trench. Deep earthquakes were observed across all the trenches. The shallow earthquakes were more prominent than intermediate and deep earthquakes in all the trenches. The seismic events in the trenches are mostly of magnitude range 3.0–4.9. This magnitude range may indicate the genesis of mild to moderate tsunamis in the trench zone in near future once sufficient slip would occur with displacement of water column.